PENGARUH KINERJA KEUANGAN, CORPORATE GOVERNANCE, DAN KUALITAS AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Ryandi Iswandika; Murtanto Murtanto; Emma Sipayung (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2014)
The purpose of this research is to determine the the influence of financial performance, corporate governance, and audit quality on corporate social responsibility disclosure. Data for this research were obtained from firm’s annual reports which is available on Indonesia Stock Exchange (IDX) sites. Samples used in this research are 139 manufacturing companies that listed on Indonesia Stock Exchange in period 2012. The Sampling technique used is purposive sampling method. This research use linear regression analysis. The tool used for this research is SPSS. Result of this research show profitability, liquidity, solvability, institutional ownership, and board of independent commissioners are not significantly influence on corporate social responsibility disclosure. Board of commissioners, audit committee, and audit quality are significantly influence on corporate social responsibility disclosure.